Botani Ekonomi Tèkay (Eleocharis dulcis) Asal Pulau Madura - Ashari Bagus Setiawan; Nunik Sri Ariyanti (The Ethnobiological Society of Indonesia, 2021)
The corms and culms of tèkay (Eleocharis dulcis, family Cyperaceae) have been used by the people in Madura for a long time, but have never been clearly disclosed in the previous publication. The purpose of this study is to examine the botanical economy including the use and socio-economic value of tèkay on the island of Madura. Exploration and specimen collection were carried out from July to August 2016 and January to March 2017 in four districts, namely Bangkalan, Sampang, Pamekasan, and Sumenep. Economic botanical data was obtained through open interviews with tèkay seekers and collectors, the shops and seller tèkay chips, and the home industry produce tèkay chips. All data obtained were analyzed descriptively. The results showed that there were two morphological variations of tèkay in Madura Island which could be distinguished based on the color of corms and culms, the shape of sterile bractea, the shape, color, and tifh hairs of the achene. This variation is a new record for the E. dulcis in Madura Island. Apart from tèkay, the Madurese know E. dulcis by several other local names: rebbha telenteyan, lhok colo'an, tèkay grobhog, tet cetet, and rokos. The corms of tèkay are used as an ingredient for making chips, dodol, porridge, and stew snacks; the culms are used as cattle feed. Direct economic value is obtained from the use of corms into tèkay chips.